The Urgency of Islamic Religious Education For Generation Z - Mursalin, Hisan; Muhammad Yusri Al Madzali (Al-Mubin, 2024)
Education plays a significant role in shaping individual personalities, society, and civilization. Education is not solely related to the knowledge imparted but also involves the formation of character, moral values, and skills needed to understand and successfully practice something new that has been learned. Education can also bring you closer to spiritual or religious values. This journal article aims to make Generation Z aware of the importance of Islamic religious education in the current digital era so that they are not easily influenced by the negative things they get from their gadgets. The research method applied in writing this journal article is a qualitative approach and literature analysis methods related to the urgency of Islamic religious education for the Zoomer Generation. This research was done by reading and analyzing relevant journals and scientific literature. The research results show a decline in Generation Z's interest in studying Islamic religious education caused by the presence of modern technology in their lives today. They feel that Islamic religious education is boring and makes them out of date, so most of them do not have the confidence to study it because they are afraid of being looked down upon by the people around them. This kind of understanding arises from their minds due to a lack of knowledge about the importance of Islamic religious education in their lives, and they also do not know the purpose and impact of this education. Therefore, this journal article aims to straighten Generation Z's understanding of the importance of Islamic religious education, especially in their current era. Providing Islamic religious education to Generation Z has a very crucial role in shaping their character. This will help them understand moral and ethical values, develop mental and emotional resilience, strengthen leadership, and build a healthy social life